2021
DOI: 10.1080/21655979.2021.2000199
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA OIP5-AS1 regulates smoke-related chronic obstructive pulmonary disease via targeting micro RNA -410-3p/IL-13

Abstract: This investigation aimed to assess the levels of serum OIP5-AS1 and micro RNA-410-3p (miR-410-3p) in patients with chronic obstructive pulmonary disease (COPD) and their potential molecular mechanism. The levels of OIP5-AS1 and miR-410-3p as well as mRNA levels of IL-13 were measured. Pearson variable linear test was applied to analyze the correlations between forced expiratory volume in 1 second (FEV1) and OIP5-AS1. The receiver operating characteristic curve was used to predict the predictive possibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
(42 reference statements)
0
20
0
Order By: Relevance
“… 43 OIP5-AS1 is a diagnostic marker for COPD, and the OIP5-AS1/miR-410-3p/IL-13 axis plays a crucial role in regulating COPD. 13 Hence, we predicted that the HDAC1-related ceRNA might contribute to clarifying the effect of HDAC1 on senescence and the role of senescence in the development of COPD. The specific role and mechanism of ceRNA in COPD need to be further verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 OIP5-AS1 is a diagnostic marker for COPD, and the OIP5-AS1/miR-410-3p/IL-13 axis plays a crucial role in regulating COPD. 13 Hence, we predicted that the HDAC1-related ceRNA might contribute to clarifying the effect of HDAC1 on senescence and the role of senescence in the development of COPD. The specific role and mechanism of ceRNA in COPD need to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of lncRNA OIP5-AS1 is elevated in CSE-stimulated 16HBE cells and can enhance the inflammation and cell apoptosis by modulating the miR-410-3p/IL-13 signaling. 13 LncRNA GAS5 functions as a ceRNA and regulates the miR-223-3p/NLRP3 axis to promote cell pyroptosis in COPD. 14 However, the role of SRGs-based ceRNA in COPD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…H9c2 cells were seeded into 96-well plate and treated with 10 µl MTT solution for 24 h. Then, 100 µl DMSO (Sigma-Aldrich) was added to each well and the plates were gently agitated for 10 min. The absorbance was determined at 490 nm using a microplate reader (BioTek) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hao and his colleagues ( Hao et al, 2021 ) revealed that the levels of opa interacting protein 5-antisense RNA 1 (OIP5-AS1) were elevated in smokers and smokers with COPD, and there was a negative connection between OIP5-AS1 and FEV 1 . Furthermore, OIP5-AS1 showed a talent in differentiating smokers with COPD from smokers, as revealed by the area under the curve (AUC) of 0.903.…”
Section: Lncrna–mirna Interaction In Chronic Inflammatory Airway Dise...mentioning
confidence: 99%
“…Thirteen lncRNAs are implicated in the physio-pathological process of COPD by sponging miRNAs ( Figure 2 ). Of these, eleven differentially expressed lncRNAs have been found in human bio-samples (including whole blood, serum, sputum, and lung tissue samples) from COPD patients: NNT-AS1 ( Mei et al, 2020 ), MEG3 ( Lei et al, 2021 ), LUCAT1 ( Zhao et al, 2021 ), SNHG5 ( Shen et al, 2020 ), CASC2 ( Liu et al, 2021a ), TUG1 ( Gu et al, 2019 ), OIP5-AS1 ( Hao et al, 2021 ), LOC729178 ( Wang et al, 2021 ), XIST ( Chen et al, 2021 ), LINC00612 ( Luo et al, 2020 ), and MIR155HG ( Song et al, 2020 ). There is a possibility that these lncRNAs could be clinically helpful in diagnosing and treating COPD.…”
Section: Clinical Implications In Chronic Inflammatory Airway Diseasesmentioning
confidence: 99%